Ethnic discrimination and depressed mood: The role of autonomic regulation. (December 2021) - Hagen, Julia M.; Sutterland, Arjen L.; Collard, Didier; de Jonge, Carien D.E.; van Zuiden, Mirjam; Zantvoord, Jasper B.; Tan, Hanno L.; van Valkengoed, Irene G.M.; van den Born, Bert Jan H.; Zwinderman, Aeilko H.; de Haan, Lieuwe; Lok, Anja
Abstract: Perceived ethnic discrimination (PED) is thought to underlie increased prevalence of depressed mood in ethnic minorities. Depression is associated with increased sympathetic and decreased parasympathetic activity. We investigated a biopsychosocial model linking PED, disrupted sympathovagal balance and depressed mood. Baseline data of HELIUS, a cohort study on health among a multi-ethnic population, was used. Heart rate variability (HRV), baroreflex sensitivity (BRS), PED (evaluated with the Everyday Discrimination Scale) and presence of depressed mood (evaluated with the Patient Health Questionnaire-9) were assessed. Associations of PED, HRV/BRS and depressed mood were analyzed with linear and logistic regression analyses. Mediation of the association of PED and depressed mood by HRV/BRS was assessed in a potential outcomes model and four steps mediation analysis. Of 9492 included participants, 14.7% fulfilled criteria for depressed mood. Higher PED was associated with depressed mood (P < .001). Lower autonomic regulation indexes were associated with depressed mood (deltaR 2  = 0.4–1.1%, P < .001) and at most weakly with PED (deltaR 2  = 0.2–0.3%, P < .001). A very modest mediating effect by HRV/BRS in the association between PED and depressed mood was attenuated after adjustment for socioeconomic status. To conclude, we found no support for the hypothesis that autonomic regulation relevantly mediates the association between PED and depression. HIGHlights: In a large multi-ethnic cohort, lower HRV and BRS indicating increased sympathetic tone were associated with depressed mood. Lower HRV and BRS were at most weakly associated with perceived ethnic discrimination. No evidence that autonomic dysregulation in response to ethnic discrimination relevantly increases chance of depressed mood.